1994
DOI: 10.1002/1097-0142(19940301)73:5<1368::aid-cncr2820730510>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum ca 125 antigen assay in patients with non-small cell lung cancer

Abstract: Background. The serum levels of CA 125 tumor‐associated antigen in patients with lung cancer have been previously related to TNM stage, histologic type, and survival rate. In the current study, the prognostic information provided by the CA 125 antigen assay was analyzed. Methods. Preoperative serum of CA 125 antigen was determined in 137 patients with non‐small cell lung cancer. The assay was performed by means of a solidphase enzyme‐immunoassay test. The influence of CA 125 serum level on postoperative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…The association of ca 19-9 with prognosis was found to be better than that of cea [16][17][18] . In contrast, other publications have reported that the use of ca 19-9 is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The association of ca 19-9 with prognosis was found to be better than that of cea [16][17][18] . In contrast, other publications have reported that the use of ca 19-9 is limited.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Clinical utility of CA-125 is thus well known but not limited to epithelial ovarian cancer with elevated levels being also associated with malignancies of endometrium, cervix, lung, breast, liver and in gastric, pancreatic, colorectal malignancies. [12][13][14] Owing to its origin from multiple epithelium of multiple tissues viz. amnion, fetal coelomic epithelium, fallopian tube epithelium and in many adult tissues, including endometrium, endocervix, pleura or peritoneum; it is amenable to elevation in benign inflammatory conditions of these epithelium and in case of structural breach.…”
Section: Introductionmentioning
confidence: 99%
“…CA125 was initially described as an ovarian cancer-associated antigen, and has recently been assayed in NSCLC. In a previous study we reported that serum levels of CA 125 provide independent information on survival and tumour relapse in patients undergoing curative surgical treatment for NSCLC (Diez et al, 1994a).…”
mentioning
confidence: 97%
“…CA125 was initially described as an ovarian cancer-associated antigen, and has recently been assayed in NSCLC. In a previous study we reported that serum levels of CA 125 provide independent information on survival and tumour relapse in patients undergoing curative surgical treatment for NSCLC (Diez et al, 1994a Analysis of tumour marker expression in NSCLC tumour tissue has not been reported as frequently. In a previous study we observed that cytosolic concentration of CEA, SCC and CA125 is a particular and distinctive characteristic of each histological type, something which could aid pathological classification (Picardo et al, 1994).…”
mentioning
confidence: 99%